Crohn Disease: FDG PET/CT Before and After Initial Dose of Anti–Tumor Necrosis Factor Therapy to Predict Long-term Response. (November 2017) - Epelboym, Yan; Shyn, Paul B.; Chick, Jeffrey Forris Beecham; Hamilton, Matthew J.; O'Connor, Stacy D.; Silverman, Stuart G.; Kim, Chun K.
Abstract : Purpose: Clinical assessments of Crohn disease activity are limited in their capacity to assess treatment response to biologic therapy. The purpose of this study was to determine if changes in FDG activity between baseline PET and repeat PET performed prior to the second dose of induction anti–tumor necrosis factor (TNF) therapy correlate with clinical response. Methods: In this prospective, institutional review board–approved, Health Insurance Portability and Accountability Act–compliant pilot study of 8 adult patients with active Crohn disease, FDG activity before and 2 weeks after initiation of anti-TNF therapy was assessed using low-dose PET/CT. FDG activity was measured in the most inflamed bowel loop using an SUVratio (SUVmax/liver SUVmean). Changes in SUVratio were compared with a blinded gastroenterologist assessment of clinical response and steroid-free remission, as well as C-reactive protein (CRP), during a 12-month follow-up period. Results: Of 8 patients, 7 showed FDG activity decline at 2 weeks, 5 of whom achieved a clinical response and steroid-free remission at 8, 26, and 52 weeks. The remaining 2 patients with FDG activity decline did not achieve a clinical response or steroid-free remission at these time points, but there were reductions in CRP. The 1 patient without FDG activity decline was a clinical nonresponder, had no reduction in CRP, and did not achieve steroid-free remission. Conclusions: A change in FDG activity at FDG PET/CT performed prior to the second induction dose of anti-TNF therapy has the potential to predict clinical response and steroid-free remission in patients with Crohn disease.